Climate Relevant Emissions from Animal Production and Reduction Potentials - Flachowsky, Gerhard; Soosten, Dirk von; Meyer, Ulrich (Animal Review, 2015)
Animal production contributes substantially to global greenhouse gas emissions (about 14.5%). The so-called Carbon Footprint (CF) considers the greenhouse gas potential of climate relevant gases (e.g., CO2 x 1; CH4 x 23; N2O x 296) and is given in CO2-eq per g or kg product or per unit edible protein. The CF may help to assess the greenhouse gas emissions associated with the production of foods of animal origin such as milk, meat, eggs or fish. The CF may contribute to sensitizing producers and consumers to a more resource-efficient and environmentally-friendly production, to the consumption of food of animal origin, and to avoiding food wastage. The highest CF per unit edible protein is calculated for products of growing ruminants (beef and lamb), followed by milk and pork and eggs and poultry meat with the lowest values. Discrepancies in the results of various studies are mainly explained by different system boundaries, allocation methods and computation of emissions, especially with regard to land use changes, enteric methane emissions and nitrous oxide emissions. A more standardized approach for data collection and CF-calculations would be a very useful tool to compare CF between production systems, regions and countries, and an indicator for food labelling, and is considered in the first part of this paper. The second part of the paper deals with the potential to reduce climate relevant gases from animal production. Some specific influencing factors, such as plant and animal breeding, feed production, animal feeding as well as animal keeping, animal health and excrement management are analysed more in detail. Most attention has been spent to the methane reduction potentials in the rumen. The reduction of CF in ruminant production per product should focus on a lowering of methane emissions from enteric fermentation and an increase of low production levels as well a reduction of ineffective animal numbers. In the future, results of plant and animal breeding may also substantially contribute to lower GHG emissions. Furthermore, new potentials to improve protein supply for human nutrition should be used. The production of food of animal origin is a very complex process and selective consideration, i.e., focussing on single factors, does not provide an assessment that reflects the complexity of the subject. Recommendations for further research activities are given.